Secretion and Delivery of Intestinal Pathogenic Escherichia coli Virulence Factors via Outer Membrane Vesicles - Rueter, Christian; Bielaszewska, Martina (Frontiers in Cellular and Infection Microbiology, 2020)
Outer membrane vesicles (OMVs) are nanoscale proteoliposomes secreted from the cell envelope of all Gram-negative bacteria. Originally considered as an artifact of the cell wall, OMVs are now recognized as a general secretion system, which serves to improve the fitness of bacteria and facilitate bacterial interactions in polymicrobial communities as well as interactions between the microbe and the host. In general, OMVs are released in increased amounts from pathogenic bacteria and have been found to harbor much of the contents of the parental bacterium. They mainly encompass components of the outer membrane and the periplasm including various virulence factors such as toxins, adhesins, and immunomodulatory molecules. Numerous studies have clearly shown that the delivery of toxins and other virulence factors via OMVs essentially influences their interactions with host cells. Here, we review the OMV-mediated intracellular deployment of toxins and other virulence factors with a special focus on intestinal pathogenic Escherichia coli. Especially, OMVs ubiquitously produced and secreted by enterohemorrhagic E. coli (EHEC) appear as a highly advanced mechanism for secretion and simultaneous, coordinated and direct delivery of bacterial virulence factors into host cells. OMV-associated virulence factors are not only stabilized by the association with OMVs, but can also often target previously unknown target structures and perform novel activities. The toxins are released by OMVs in their active forms and are transported via cell sorting processes to their specific cell compartments, where they can develop their detrimental effects. OMVs can be considered as bacterial “long distance weapons” that attack host tissues and help bacterial pathogens to establish the colonization of their biological niche(s), impair host cell function, and modulate the defense of the host. Thus, OMVs contribute significantly to the virulence of the pathogenic bacteria.